Pengembangan Buku Portofolio Literasi Berbasis Ajaran Tri-N untuk Meningkatkan Kemampuan Menulis Siswa Sekolah Dasar - Dewi Wulandari; Akbar Al Masjid (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to improve the writing skills of fable stories in grade V students. The type of research used is R&D (Research and Development) or development research. This development research uses the ADDIE development model (Analysis, Design, Development, Impementation, and Evaluation). The researcher has developed a literacy portfolio book based on Tri-N teaching for students' writing skills. Data collection was conducted by observing the learning process, interviewing educators, tests in the form of pre and post tests, and questionnaires to determine student and teacher responses. Data collection is supported by documentation of the implementation of learning by applying the product. The results of research using this development product can be said to be feasible based on the assessment of media experts and linguists. Based on the results of the pre test, post test, teacher response, and student response, the use of Tri-N teaching-based literacy portfolio books can improve the writing skills of fifth grade elementary school students so that it can be said that this product is effective.,